EVOLUTION OF DIRECTIVE PRINCIPLES OF STATE POLICY - Srinibas Nayak , Akash Trikha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The State Political Guidelines for the development of economic democracy in India include guidance for both the state and people. In India, the constitution makers did not impose a particular economic structure on citizens but instead sought to suggest a structure more suited to Indian circumstances. The Directive Principles of State Policy are constitutional rights generally composed of socio-economic and cultural rights reflected in the form of duties, on the state without reciprocal rights to the people. The adoption by different countries of this definition of the Directive Principles of State Policy is based on one political or economic purpose and, if not on the other, countries believe that the implementation of these principles and goals would support if not eradicate it. No doubt the two countries under analysis-India and Nigeria had their fair share of the above-mentioned problems and experiences. Hence, this research paper discusses the evolution of this concept in Indian and Nigerian constitutional creation.